Nutritional Deficiency–Related Oral and Cutaneous Lesions in an Obese Patient. (January 2018) - Esquivel-Pedraza, Lilly; Méndez-Flores, Silvia; Cicero-Casarrubias, Alba; Saeb-Lima, Marcela; Domínguez-Cherit, Judith; Fernández-Cuevas, Laura
Abstract : Abstract: The cutaneous and oral lesions related to nutritional deficiencies are scarcely reported. Micronutrient deficiencies may significantly affect mouth mucosa and skin, causing great morbidity. We report an extraordinary case with detailed clinical and microscopic findings affecting the oral cavity and skin. Physicians must be familiar with these manifestations to suspect the diagnosis.